uation of Protection Against Collapse from Buckling of Stiffened Column Based on ASME BPVC Sec. VIII Div.2 Using Finite Element Simulation - Purwo adarno (ICON-CSE, 2014)
Aprotection against collapse from buckling of a stiffened column was evaluated based on ASME Boiler and Pressure Vessel Code Section VIII Division 2 using the finite element simulation. The column without the stiffener ring was also evaluated as a comparison. A finite element code ANSYS ver. 14.5 was used to perform thebuckling analysis of the columns. The linear (eigenvalue) buckling analysis was performed to obtain a critical load factor then the value was compared with the minimum design factor required based on the ASME Code. The columns was modeled using a shell element and the geometric non-linearties was not considered. The external pressure, the self-weight force and the temperature load were considered as the loading in the analysis. Among all applied loads, the external pressure was the most significant load contributing for the buckling of this column. The buckling strength of the column was greatly improved by the utilization of the stiffener ring, and the design stiffened column satisfied the requirement for protection against collapse from buckling.